1998
DOI: 10.1111/j.2044-8325.1998.tb00666.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between individual personality orientation and executive leadership behaviour

Abstract: The following study was undertaken to explore the link between individual differences in personality orientation and subsequent leadership behaviours in the workplace. More specifically, relationships among two measures of personality and one measure of transformational–transactional leadership style were investigated using data collected from 253 senior executives (and their direct reports) from a highly diversified global corporation. After an initial examination of the personality variables using a correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 34 publications
3
59
0
Order By: Relevance
“…Over the last decade or so, numerous theoretical models and several empirical studies have sought to identify personality traits of charismatic and transactional leaders (e.g., Bono & Judge, 2004;Church & Waclawski, 1998;Crant & Bateman, 2000;De Hoogh et al, 2005;Hetland & Sandal, 2003;House & Howell, 1992;Howell & Avolio, 1993;Howell & Higgins, 1990;Judge & Bono, 2000;Kuhnert & Lewis, 1987;Ployhart et al, 2001;Ross & Offermann, 1997;Sosik, Avolio, & Jung, 2002;Sosik & Dworakivsky, 1998). Together these conceptual models and empirical studies suggest that various personality traits are possible antecedents of charismatic and transactional leader behavior.…”
Section: Charismatic and Transactional Leadershipmentioning
confidence: 96%
“…Over the last decade or so, numerous theoretical models and several empirical studies have sought to identify personality traits of charismatic and transactional leaders (e.g., Bono & Judge, 2004;Church & Waclawski, 1998;Crant & Bateman, 2000;De Hoogh et al, 2005;Hetland & Sandal, 2003;House & Howell, 1992;Howell & Avolio, 1993;Howell & Higgins, 1990;Judge & Bono, 2000;Kuhnert & Lewis, 1987;Ployhart et al, 2001;Ross & Offermann, 1997;Sosik, Avolio, & Jung, 2002;Sosik & Dworakivsky, 1998). Together these conceptual models and empirical studies suggest that various personality traits are possible antecedents of charismatic and transactional leader behavior.…”
Section: Charismatic and Transactional Leadershipmentioning
confidence: 96%
“…Research shows that transformational leaders put greater emphasis on innovation than transactional leaders (Church & Waclawski, 1998;Howell & Higgins, 1990). In addition, recent research found a positive relationship between transformational leadership and organizational innovation (Gumusluoglu & Ilsev, 2009;Jung, Chow, & Wu, 2003;Jung, Wu, & Chow, 2008).…”
Section: Transformational and Transactional Leadership And Innovativementioning
confidence: 99%
“…For example, Church and Waclawski (1998) have studied the relationship between individual orientation, measured through the MBTI and executive leadership.…”
Section: Leadership and Successionmentioning
confidence: 99%